INTEGRATION OF ISLAMIC ETHICAL VALUES IN STRATEGIC LEADERSHIP AT ISLAMIC RELIGIOUS EDUCATIONAL INSTITUTIONS - Achmad Faizal Ababil; Misbahul Arifin (Irfani, 2025)
This study looks at how Islamic moral qualities including trust (amanah), justice (ʿadl), honesty (ṣidq), and tabligh are used in strategic leadership at SMK Nurul Abror Al Robbaniyin. Using a qualitative technique with a case study design, interviews were done with the principal, vice principal, and institutional managers, and participatory observations were collected. These results reveal that these principles are utilized to handle administration and finance, communicate inside the institution, make decisions, and divide up roles. These results help us learn more about the type of Islamic educational leadership that is both morally and spiritually right and good for managing. Islamic ethics builds a company culture that is transparent, responsible, and encourages everyone to get involved. By putting these values into practice, leaders not only show that they are moral people, but they also create a management system that makes sure that institutions are good and that everyone is treated fairly. In theory, this study helps to create a framework for value-based leadership in Islamic education. To reach this goal, this research suggests improving value-based leadership training and doing more research in other settings of other Islamic institutions to make a more adaptable ethical leadership model that can change with the times.